Design and CFD analysis of an industrial low-pressure compressor for a concentrating high-temperature solar power plant - Cuturi,N; Aronica,S; Bellini,L; Salvati,A (International journal of applied thermodynamics, 2019)
The increasing need of renewable energy sources leads to the study of different alternative power plants. One of them is the thermo-electrical conversion by solar concentration power plants with an open volumetric receiver, using non-pressurized air as the heat transfer fluid. Due to the poor heat transfer characteristics, a large air mass flowrate is needed in the solar tower to transfer a sufficient amount of heat to a conventional steam power cycle. The subject of this study is a solar-thermal plant with 100 MW electrical power output. The intermediate heat transfer fluid, air, circulates in a semi-open circuit, and 1.125 compression ratio is required by the forced convection circuit. The inherently high air temperatures and mass flowrate require the design of a compressor from scratch, which is the aim of this study. The design starts from the selection and the sizing of the compressor, based on the standard mono-dimensional turbomachinery theory, and continue with the verification of its fluid dynamic performance, based on a commercial CFD code (ANSYS-FLUENT). A 2D case is evaluated first, to ensure that the geometry is working correctly, and then the full 3D geometry is simulated to quantify the real performance of the compressor. A preliminary structural analysis of the blade is also performed to verify the structural integrity of the chosen configuration.